29 The race to reperfusion: determinants of total ischaemic time in an irish STEMI population. (16th October 2019) - O'Connor, C; Maguire, C; Ibrahim, A; Kumar, R; Kumar, J; Buckley, A; Ahearne, C; Cahill, C; Hennessy, T; Arnous, S; Kiernan, T
Abstract : Ireland benefits from a highly functioning primary percutaneous coronary intervention (PPCI) programmes, but despite this STEMI is still associated with significant morbidity and mortality. The European Society of Cardiology updated the STEMI guidelines in 2017, and with them introduced a novel metric relating to STEMI patients: 'total ischaemic time'. This time-period starts at the onset of chest pain and ends at wire cross, and it is thought to accurately reflect burden of myocardial destruction. The guidelines also introduce striker guidance on timelines, in order to minimise systemic delay. This study aimed to assess the total ischaemic time of patients presenting with STEMI in an Irish tertiary referral centre and the factors influencing delays in presentation and treatment. Methods: Prospective cohort analysis was conducted on all patients presenting to University Hospital Limerick with STEMI from October 2017 to January 2019. Patients were included if they had a culprit lesion that was successfully revascularized. Baseline demographics were recorded at time of presentation. Bayesian statistics were employed to conduct the analysis. Results: 158 patients were recruited. Mean age was 61(range29–96). Male:female ratio 5:1 in this cohort. Average total ischaemic time was 409.4 mins±501.4. The average time from chest pain to 'call for help' (i.e. patient delay) was 208.3 mins±397.8, which represented 50.89% of the total ischaemic time (See figure 1 ). The average time from 'call for help' to first medical contact (FMC) was 18.4 mins±30.07. Average time from FMC to ECG was 44.9 mins±151.16, and was dependent upon type of FMC (Primary care 127 mins vs paramedic 25 mins p=0.030932). After FMC, 48.7% of patients had an ECG performed in under 10 mins as per guidelines. After ECG was performed, 46.4% of patients had ECG to 'wire cross' time under 90 mins as per guidelines; 65.8% were within 120 mins and 91.4% were within 180 mins. Those presenting to their general practitioner as FMC were significantly less likely to have both an ECG in <10 mins (NNH 2.84 95%CI 1.79–6.91) and ECG to wire time of <90 mins (NNH 6.13 95%CI 2.88–48.70). As age increased, so too did total ischaemic time (Pearson R=0.164, p=0.043), which was dependent on increasing patient delay with age (Pearson R=0.2181, p=0.0066). Women had a higher total ischaemic time than men (546 vs 382 mins p=0.0233). This was determined to be as a result of: a numerically higher patient delay (220 vs 206 mins, p=0.214) and women having a longer time from FMC to ECG (104 mins vs 34 mins, p=0.0021). Conclusion: Over 50% of the total ischaemic time was before patients called for help, suggesting a role for cardiovascular awareness programmes. Increasing age was associated with longer patient delay, indicating a need for directed awareness in this demographic. Women had a higher total ischaemic time, and waited a significantly longer time for ECG following FMC; highlighting the need for awareness amongst healthcare professionals of atypical clinical features associated with STEMI in women. Patients who attended their GP waited longer for an ECG and, once performed, were less likely to be revascularised within 90 mins.